Impact of discontinuing automatic reflex urine culture after urinalysis: a diagnostic and antibiotic stewardship initiative - Berger, Blaine; Lukey, Janell; Jinadatha, Chetan; Navarathna, Dhammika H. (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionThis study aims to assess the impact of discontinuing reflex urine cultures based on urinalysis results (positive for nitrates and/or leukocyte esterase) on diagnostics,antibiotic usage, and laboratory efficiency at the Central Texas Veterans’ HealthCare System (CTVHCS). It seeks to evaluate whether stopping reflex testing reducesunnecessary antibiotic use, enhances antibiotic stewardship, and improves theprocessing of clinically relevant specimens.MethodsA 6-year retrospective analysis was conducted, comparing data from 3 years before and 3 years after the 2018 policy change, which discontinued reflex urine culture unless specifically requested by healthcare providers suspecting urinary tract infection (UTI) symptoms. The study analyzed the number of processed urine cultures, positivity for uropathogens, and antibiotic usage trends before and after the policy change.ResultsThe policy change resulted in a significant reduction in processed urine cultures. There was also a notable decrease in ciprofloxacin usage and an increase in the use of nitrofurantoin,indicating a shift towards narrower-spectrum antibiotics.DiscussionStopping reflex testing reduced the lab burden by focusing on clinically relevant cases of UTIs and supported improved antibiotic stewardship. This enabled healthcare providers toselectively order culture and sensitivity, targeting true UTIs.